Progress on research and development of goji berry drying: a review - Cui, Chaojing; Zhao, Dandan; Huang, Jin; Hao, Jianxiong (International journal of food properties, 2022)
Goji berry, as a kind of typical and special agricultural material, has high water content, high sugar content, thin epidermis with waxy covering, and dense fleshy cell structure, which makes the drying process more complex than the dehydration of other bio-materials. To obtain high drying efficiency and the high quality products, most researchers have paid much attention on the different kinds of pretreatment and drying technology. This study aimed to examine all the corresponding published data in the literature and to compare the drying characteristics and quality of wolfberry dried by conventional and advanced wolfberry drying methods as well as different drying parameters. We conclude that heat pump drying with simultaneous control of temperature and humidity could replace traditional hot air drying in commercial production to increase the drying efficiency and quality of wolfberry. Infrared drying and microwave drying can be combined with other drying methods to improve drying efficiency; freeze drying, pulsed vacuum drying and electro-hydrodynamic drying are conducive to maintain the appearance and nutrients as well as higher rehydration ratio because of more porous microstructure compared with hot air drying. In addition, this study gives some suggestions and new horizons for directed wolfberry drying development both on the research and application in the future.